Deer mouse hemoglobin exhibits a lowered oxygen affinity owing to mobility of the E helix. Issue 4 (2nd April 2013) - Inoguchi, Noriko; Oshlo, Jake R.; Natarajan, Chandrasekhar; Weber, Roy E.; Fago, Angela; Storz, Jay F.; Moriyama, Hideaki
<x xml:space="preserve">Abstract</x> The deer mouse, Peromyscus maniculatus, exhibits altitude‐associated variation in hemoglobin oxygen affinity. To examine the structural basis of this functional variation, the structure of the hemoglobin was solved. Recombinant hemoglobin was expressed in Escherichia coli and was purified by ion‐exchange chromatography. Recombinant hemoglobin was crystallized by the hanging‐drop vapor‐diffusion method using polyethylene glycol as a precipitant. The obtained orthorhombic crystal contained two subunits in the asymmetric unit. The refined structure was interpreted as the aquo‐met form. Structural comparisons were performed among hemoglobins from deer mouse, house mouse and human. In contrast to human hemoglobin, deer mouse hemoglobin lacks the hydrogen bond between α1Trp14 in the A helix and α1Thr67 in the E helix owing to the Thr67Ala substitution. In addition, deer mouse hemoglobin has a unique hydrogen bond at the α1β1 interface between residues α1Cys34 and β1Ser128.